Chapter 6. Evelyn Briggs Baldwin and the Quereau Glacier - Lanning, Jacqueline (Septentrio Conference Series, 2015)
On September 20, 1898, during the second Wellman polar expedition, Wellman’s second-in-command, Evelyn Briggs Baldwin, gave the name ‘Quereau’ to a glacier on the west coast of Wilczek Land. There is no direct evidence, as of this writing, that can be found on why he described this feature as a ‘Querean’ glacier. However, there is indirect evidence supporting the notion that he named the glacier after a geology professor, Edmund Chase Quereau.